The existence of solution of nonlinear problem of magnetization - Katauskis, Pranas (Lietuvos matematikos rinkinys, 1999)
The kinetic equations describing the magnetization of a medium consisting of single-domain particles are investigated. The local existence of solution and its uniqueness is proved.